2007
DOI: 10.1097/gim.0b013e31802f78d6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a newborn screening follow-up algorithm for the diagnosis of isobutyryl-CoA dehydrogenase deficiency

Abstract: Purpose: Isobutyryl-CoA dehydrogenase deficiency is a defect in valine metabolism and was first reported in a child with cardiomyopathy, anemia, and secondary carnitine deficiency. We identified 13 isobutyryl-CoA dehydrogenasedeficient patients through newborn screening due to an elevation of C 4 -acylcarnitine in dried blood spots. Because C 4 -acylcarnitine represents both isobutyryl-and butyrylcarnitine, elevations are not specific for isobutyryl-CoA dehydrogenase deficiency but are also observed in short-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…Urinary organic acids did not show elevation of butyrylglycine or isobutyrylglycine. The patient was treated with carnitine which reversed the cardiomyopathy and development was normal (5,10).…”
mentioning
confidence: 98%
“…Urinary organic acids did not show elevation of butyrylglycine or isobutyrylglycine. The patient was treated with carnitine which reversed the cardiomyopathy and development was normal (5,10).…”
mentioning
confidence: 98%
“…The original patient presented with anemia and dilated cardiomyopathy (Roe et al 1998 ). Thus far, at least 22 individuals have been described who are mostly asymptomatic, largely identifi ed via newborn screening (Koeberl et al 2003 ;Sass et al 2004 ;Oglesbee et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…She has remained well since. Of the additional patients whom we have had the opportunity to study (all identified through newborn screening), all but one have remained asymptomatic [22]. The symptomatic patient had recurrent episodes of emesis and dehydration with mild intercurrent illness accompanied by dramatic increase in the production of isobutyryl-CoA intermediates and their carnitine derivatives.…”
Section: Acyl-coa Dehydrogenasesmentioning
confidence: 99%
“…Given our then understanding of isovaleric acidemia it was logical to assume that the severe medical problems exhibited by both patients could be attributed to their enzymatic blocks. However, soon babies with both deficiencies began to be flagged through newborn screening and all was not as straightforward as one might hope [21,22].…”
Section: Acyl-coa Dehydrogenasesmentioning
confidence: 99%